Evaluation of The Hygiene Procedures and Commitment to Food Safety of Calapan City Street Food Vendors (American Journal of Multidisciplinary Research and Innovation, 2023)
This study assessed the relationship between the hygiene practices and procedures of street food vendors and the level of food safety in Calapan City. The research addresses the need for a practical intervention to improve hygiene practices among street food vendors, ensuring the safety of consumers in Calapan City and promoting responsible business practices. The study utilized a descriptive-correlational research design, employing the Pearson Product Moment Correlation Coefficient as a statistical tool to determine the relationship between hygiene practices and food safety. The respondents consisted of 30 volunteer street food vendors and customers in Calapan City. Findings revealed that, in the new normal, street food vendors in Calapan City maintain a satisfactory level of hygiene practices and procedures, meeting cleanliness standards. Utensils and equipment are regularly cleaned and sanitized, reducing health risks and illnesses. Rresults also showed that there is a significant relationship between the status of hygiene practices and procedures of street food vendors and the level of food safety of the street food sold in Calapan City with computed r-value of 0.631. Based on the results, the researchers recommend that food business owners and staff acquire adequate knowledge and awareness of proper food safety practices and adhere to them consistently in their operations. By conducting this study, the authors contribute to the improvement of hygiene standards and food safety in the street food sector, enhancing the overall well-being of consumers and supporting the growth of responsible and safe street food businesses in Calapan City.